Electromagnetic fields in linear and nonlinear chiral media: a time-domain analysis - Ioannis G. Stratis; Athanasios N. Yannacopoulos (Abstract and Applied Analysis)
We present several recent and novel results on the formulation and the analysis of the equations governing the evolution of electromagnetic fields in chiral media in the time domain. In particular, we present results concerning the well-posedness and the solvability of the problem for linear, time-dependent, and nonlocal media, andresults concerning the validity of the local approximation of the nonlocal medium (optical response approximation). The paper concludes with the study of a class of nonlinear chiral media exhibiting Kerr-like nonlinearities, for which the existence of bright and dark solitary waves is shown.